Advances in experimental political science - Druckman, James N., 1971-; Green, Donald P., 1961- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
'Experimental political science has changed. In two short decades, it evolved from an emergent method to an accepted method to a primary method. The challenge now is to ensure that experimentalists design sound studies and implement them in ways that illuminate cause and effect. They must do so while also respecting ethical boundaries, interpreting results in a transparent manner, and sharing data and research materials to ensure others can build on what has been learned. This book explores the application of new designs; the introduction of novel data sources, measurement approaches, and statistical methods; the use of experiments in more areas; and discipline-wide discussions about the robustness, generalizability, and ethics of experiments in political science. The volume explores these new opportunities while also highlighting the concomitant challenges. The goal is to help scholars and practitioners conduct high-quality experiments that make important contributions to knowledge'--
Includes bibliographical references and index.
Keywords: Political science -- Methodology; Political science -- Research; Political science -- Experiments